2017
DOI: 10.1001/jamapsychiatry.2017.2124
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Dementia Care Management in Primary Care

Abstract: clinicaltrials.gov Identifier: NCT01401582.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
195
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(203 citation statements)
references
References 50 publications
1
195
1
6
Order By: Relevance
“…Other models include addressing the needs of family caregivers simultaneously with comprehensive disease management of people living with dementia to improve the quality of life of both 498 . Several evaluations have suggested that such approaches have considerable potential for improving outcomes for people with dementia and their family caregivers (for example, delayed nursing home admission and reduction in caregiver distress) 499‐508 . Current research is attempting to determine the feasibility of these models beyond the specialty settings in which they currently operate 509‐512 …”
Section: Caregivingmentioning
confidence: 99%
See 1 more Smart Citation
“…Other models include addressing the needs of family caregivers simultaneously with comprehensive disease management of people living with dementia to improve the quality of life of both 498 . Several evaluations have suggested that such approaches have considerable potential for improving outcomes for people with dementia and their family caregivers (for example, delayed nursing home admission and reduction in caregiver distress) 499‐508 . Current research is attempting to determine the feasibility of these models beyond the specialty settings in which they currently operate 509‐512 …”
Section: Caregivingmentioning
confidence: 99%
“…498 Several evaluations have suggested that such approaches have considerable potential for improving outcomes for people with dementia and their family caregivers (for example, delayed nursing home admission and reduction in caregiver distress). [499][500][501][502][503][504][505][506][507][508] Current research is attempting to determine the feasibility of these models beyond the specialty settings in which they currently operate. [509][510][511][512] In 2016, the National Academies of Sciences, Engineering, and Medicine released Families Caring for an Aging America, a seminal report that includes a number of recommendations to refocus national health care reform efforts from models of care that center on the patient (person-centered care) to models of care that also explicitly engage and support the patient's family (family-centered care).…”
Section: Enhancing Health Care For Family Caregiversmentioning
confidence: 99%
“…In this service model, people living with dementia are allocated a care manager to coordinate care, facilitate collaboration between services and usually deliver care [49][50][51][52][53]. Dementia case management interventions have been associated with greater benefits for patient and carers if they are: for 6 months or more; multi-disciplinary, interprofessional, and delivered by a case worker with a skilled background (e.g.…”
Section: Dementia Case Management (Collaborative Care/care Coordination)mentioning
confidence: 99%
“…This analysis is based on data from a telephone-based questionnaire and semi-structured interview assessment in a convenience sample of n=141 people with cognitive impairment in the primary care setting in Mecklenburg-Western Pomerania and North-Rhine-Westphalia, respectively. Participants were recruited from currently running interventional trials intersec-CM (Supporting elderly people with cognitive impairment during and after hospital stays with intersectoral care management) [30] and the DCM:IMPact study (Dementia Care Management: Implementation into different Care Settings), an implementation study of the dementia care management of the DelpHi-MV trial [31][32][33]. The assessments were conducted during the time of the lockdown during study contacts between 22 nd of March and 5 th of June 2020, before restrictions were lifted.…”
Section: Methodsmentioning
confidence: 99%
“…DCM:IMPact complements the DelpHi-trial (Dementia: Lifeand person-centered help). In this study, the effective [32] and cost-e cient [33] dementia care management is implemented in different care settings, including ambulatory care services, dementia care networks, and hospitals.The study aims to evaluate various care setting for need and implementation barriers for such a model of care, and in how its effects could be optimized. The DCM:IMPact study started in 2019.…”
Section: Samplementioning
confidence: 99%